Bromodomain-containing 4 as a therapeutic target in inflammatory bowel diseases and colorectal cancer - Marafini, Irene; Frascatani, Rachele; Colella, Marco; De Cristofaro, Elena; Monteleone, Giovanni (Frontiers in Pharmacology, 2025)
Bromodomain-containing protein 4 (BRD4), a component of the bromodomain and extraterminal domain (BET) family, acts as a scaffold for transcription factors at promoters and super-enhancers, with the downstream effect of positively regulating the activity of signaling pathways, which sustain the inflammatory properties of immune cells and the expression of oncogens. These discoveries have boosted an intensive experimental work aimed at exploring the involvement of BRD4 in the pathogenesis of immune-mediated diseases and malignancies. As a result of these studies, there has been a considerable interest in the development of BRD4 inhibitors, which are now ready to be tested in clinical trials. In this article, we review the data about the expression and role of BRD4 in patients with Crohn’s disease and patients with ulcerative colitis, the major human inflammatory bowel diseases (IBD), as well as in patients with colorectal cancer (CRC). We also discuss the more recent data supporting the therapeutic benefit of BRD4 inhibitors in both IBD- and CRC-like mouse models.